The Berlin Republic : German unification and a decade of changes - Gellner, Winand; Robertson, John Douglas, 1952- (F. Cass, 2003)
These essays offer fresh insight and perspectives explaining the effects of East Germany's unification into the western system on Germany and the EU as a whole.